The Effect of Skincare Review Content on Fulfilling Information Needs on Youtube Channels - Lestari, Anggita; Melinda, Denay; Putri, Shinta Hartini (Budapest International Research and Critics University, 2022)
Beauty Vlogger is a content creator who provides beauty information to his audience, usually beauty vlooger reviews a beauty product and also recommends a skincare product. One of the beauty vloggers who likes to review beauty products is Mary Angline. Mary Angline often makes videos with a beauty theme, namely with video content reviewing beauty products, one of which is skincare to fulfill the information needs of her audience, viewers who watch Mary Angline's content also comment. This study aims to determine the effect of skincare review content on meeting the information needs of commentators on the video